Photo-voice as a qualitative research method in nursing and health sciences: A literature review - . Asniar; Urai Hatthakit; Wantanee Wironpanich (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
The interest on research methods using photograph and photo-interview has emerged in the last decade. However, some aspects of this method were less explained for further application. This review revealed the state of knowledge of photo-voice in qualitative nursing and health researches in order to provide an updated description on this method. Photo-voice is one of visual research methods to elicit information through participant-produced photographs and photo interview. The objective of this review was to explore the current applications of photo-voice regarding to the terms used, the framework underpinning the researches, the research designs, the concepts explored, the advantages and disadvantages identified and the guideline provided for future use. Based on the literature reviewed, photo-voice has proved its applicability to address sensitive issues and to provide richer data and deeper analysis. This research method could improve the comprehensiveness of the data produced and increase the participation of groups being investigated.The rich visual and narrative data collected by this method are considered appropriate to be applied in exploring the marginalized groups in a way that empower them. This method also opens the chance to involve other disciplines in a research team. Some issues to consider in applying this method are time-consuming and technical limitatiosn, as well as the challenges in maintaining the level of participation. However, the advantages of the method were more prominent, especially in balancing the power in research and empowering the participants. This method was recommended to use in researches conducted in oppressed or marginalized groups for the purpose of empowerment and producing indigenous knowledge of the groups